Análisis del estrés de transferencia de la secuencia de terremotos de Turquía, Mw7.8 y Mw7.5, 2023 - Carrera Cevallos, Amilcar Wilfrido (2023)
This document describes the changes that have been achieved during the two great earthquakes that hit Turkey with different epicenters. On February 6, 2023, an earthquake of = 7,8 occurred south of Turkey, with an epicenter near the north ern border of Syria. This telluric event had a second earthquake 9 hours later, by a movement of = 7,5 about 90 km to the north. The earthquake = 7,8 and inscribed aftershocks can be found in the transition zone of faults two faults: the Dead Sea and Eastern Anatolia. The earthquake with its preliminary location is placed near a triple junction: Arabian and African plates and finally the Anatolian block. This last fault adapts the westward movement of Turkey towards the Aegean Sea; on the other hand, the Dead Sea fault adapts the northward movement of Arabia in its peninsula about the African plate. The event broke a seismic gap more than 200 kilometers long and 40 kilometers wide. The aim is to contribute and raise awareness of the transfer stress role of Turkey’s evolving earthquake sequence. Providing tools and knowledge will help forecast the future distribution of aftershocks, thus allowing considering the possibility of subsequent primary earthquakes; although it is preliminary hope that it will be timely; being a starting point for future earthquakes of equal or greater magnitude.